Brain-derived neurotrophic factor as a driving force behind neuroplasticity in neuropathic and central sensitization pain: a new therapeutic target? - Nijs, Jo; Meeus, Mira; Versijpt, Jan; Moens, Maarten; Bos, Inge; Knaepen, Kristel; Meeusen, Romain (Expert opinion on therapeutic targets, 2015)
Introduction: Central sensitization is a form of maladaptive neuroplasticity underlying many chronic pain disorders, including neuropathic pain, fibromyalgia, whiplash, headache, chronic pelvic pain syndrome and some forms of osteoarthritis, low back pain, epicondylitis, shoulder pain and cancer pain. Brain-derived neurotrophic factor (BDNF) is a driving force behind neuroplasticity, and it is therefore crucial for neural maintenance and repair. However, BDNF also contributes to sensitization of pain pathways, making it an interesting novel therapeutic target.Areas covered: An overview of BDNF's sensitizing capacity at every level of the pain pathways is presented, including the peripheral nociceptors, dorsal root ganglia, spinal dorsal horn neurons, and brain descending inhibitory and facilitatory pathways. This is followed by the presentation of several potential therapeutic options, ranging from indirect influencing of BDNF levels (using exercise therapy, anti-inflammatory drugs, melatonin, repetitive transcranial magnetic stimulation) to more specific targeting of BDNF's receptors and signaling pathways (blocking the proteinase-activated receptors 2-NK-κβ signaling pathway, administration of phencyclidine for antagonizing NMDA receptors, or blockade of the adenosine A2A receptor).Expert opinion: This section focuses on combining pharmacotherapy with multimodal rehabilitation for balancing the deleterious and therapeutic effects of BNDF treatment in chronic pain patients, as well as accounting for the complex and biopsychosocial nature of chronic pain.